Desmoplastic fibroma of the temporal bone - Garov, E V; Kaloshina, A S; Mishchenko, V V; Garova, E E (Vestnik otorinolaringologii, 2016)
This paper reports a case of the extremely rare disease, the desmoplastic fibroma of the temporal bone (DF). The clinical course of this pathology, the methods for its diagnostics, and surgical treatment are described.